Effects of Summer Rainfall on the Soil Thermal Properties and Surface Energy Balances in the Badain Jaran Desert - Jiangang Li; Ali Mamtimin; Zhaoguo Li; Cailian Jiang; Minzhong Wang (Advances in Meteorology)
Based on observational data collected during the summer of 2009 from the southern Badain Jaran Desert, the surface sensible and latent heat fluxes and shallow soil thermal storage were obtained through corrections and quality control measures. The soil thermal properties and characteristics of the land surface energy budget before and after rainfall episodes were systematically analyzed. Short-term precipitation had a greater influence than systematic precipitation on the soil temperature (ST) and soil volumetric water content (VWC). After rainfall, the VWC rapidly increased, showing a decreasing growth rate trend with depth and time in all layers; the soil temperature change rate (TCR) exhibited the opposite tendency. The surface albedo, which was affected little by the solar elevation angle and short-term precipitation, fluctuated from low to high during short-term rainfall. The soil thermal parameters, including the volumetric heat capacity, thermal conductivity, and diffusivity, all increased after rainfall. The diurnal soil heat flux variations in each layer manifested as quasisinusoids, and the amplitude gradually decreased with depth. The energy balance ratio (EBR) without and with soil heat storage (S) varied differently; after incorporating S, the EBR increased by approximately 5-6% regardless of rainfall but remained lower afterward. Throughout the observation period, the maximum daytime EBR appeared approximately 1-2 days before or after rainfall and gradually declined otherwise. These findings are fundamental for understanding the influences of cloud and precipitation disturbances on radiation budgets and energy distributions and improving the parameterization of surface radiation budgets and energy balances for numerical models of semiarid areas.